IMPACT AND MITIGATION OF LIGHTNING ON STRUCTURES AND INFRASTRUCTURE - Tanwer, M. Tamim; Pandey, Anchal U.; Dhimmar, Devanshu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Lightning poses a dual threat to buildings through direct and indirect strikes. Damage resulting from a direct strike includes the shattering of wood, windows, masonry, and other poorly conductive materials, as well as the burnout of electrical power and distribution equipment. Energy distribution transformers may also burst due to the impact of a direct lightning strike. On the other hand, indirect strikes can affect telecommunications lines, electricity cables, instrument data cables, and even underground plumbing, potentially carrying damaging lightning surges into a building. Certain fiber-optic cables may prove inadequate in providing sufficient protection. To safeguard structures from potential harm, two prominent technologies are employed: the Stormaster Early Streamer Emission Terminal and the Benjamin Franklin Rod. The former is the more commonly adopted approach, leveraging contemporary protective system technologies. Extensive research conducted during our project indicates that damage to a structure caused by an Early Streamer Emission terminal is less severe than that which would result from traditional lightning protection methods. An innovative advancement in this realm is the Non-Electronic Lightning Terminal, considered a more promising approach than its electronic counterpart. Further research on non-electronic lightning terminals, both in conceptualization and practical application, holds the potential to provide clearer insights into their efficacy and benefits.